A history of scientific journals : publishing at the Royal Society, 1665-2015 /: publishing at the Royal Society, 1665-2015. (2022) - Fyfe, Aileen; Moxham, Noah; McDougall-Waters, Julie; Røstvik, Camilla Mørk
No abstract available